The Impact of the U.S.–India Civil Nuclear Agreement on Nuclear Development in India - Sulemana, Andi Ahmad Husain Ramadhana; Burhanuddin, Agussalim; Abdullah, Nurjannah (Glocal Society Journal, 2024)
The U.S.–India Civil Nuclear Agreement, signed in 2008, marked a significant turning point in India's nuclear development. This landmark agreement ended decades of international isolation for India’s civilian nuclear program, enabling access to global nuclear technology and fuel markets. By fostering collaboration with major nuclear suppliers, the deal aimed to boost India's nuclear energy capacity while reinforcing its non-proliferation commitments. This study aims to show that the U.S.–India Civil Nuclear Agreement plays a crucial role in the development of domestic energy capacity by increasing nuclear energy capacity, while also enhancing India's global status by strengthening its international legitimacy as a country with a peaceful nuclear program free from NPT restrictions. Additionally, the agreement opens access to advanced reactor technology and global markets, strengthens strategic capabilities through dual-use technology, but also presents challenges such as legal barriers, social resistance, and geopolitical risks from neighboring countries.